From Crossroads to Cultural Destination: Reimagining Lamia’s Role in Greece’s North-South Continuum Through Heritage-Driven Tourism - Pineli, Triantafyllia (Technical Annals, 2025)
The old city of Lamia, today the core of the enlarged (Callicrates’) Municipality of Lamia, is a medium-sized city located roughly in the heart of Greece. [Figures 1 – 2] Its advantages include its geographical location, its rich historical past, its monumental constructions and ruins, the beautiful nature that surrounds it and its interesting intangible cultural heritage. In the context of this research, an effort was undertaken to formulate a systematic methodology—delineated in the second part of this paper—aimed at addressing a pivotal question: to what degree, if at all, the contemporary tourist influx in the city correlates with the management practices of the cultural heritage within its broader region. The first impression that is easily given, therefore, is that Lamia is characterized by limited visitor numbers, which makes it introverted and contributes to the reduced pleasure of its citizens from daily life there. The last ones declare that they observe problems in aesthetics, urban planning, cultural activity and the way of protecting and promoting their cultural heritage. The methodical collection and evaluation of data from bibliography, on-site observations, interviews and official sources, such as ELSTAT (Hellenic Statistical Authority) and EUROSTAT, indicate that there is indeed a relationship between cultural and tourist activity and that taking various measures with the aim of strengthening the former in Lamia could contribute gradually, with patience and persistence, to improving its position on the cultural and tourist map of Greece, as has also happened in the case of other European cities in recent decades.